Access Sites for TAVI: Patient Selection Criteria, Technical Aspects, and Outcomes - Biasco, Luigi; Ferrari, Enrico; Pedrazzini, Giovanni; Faletra, Francesco; Moccetti, Tiziano; Petracca, Francesco; Moccetti, Marco (Frontiers in Cardiovascular Medicine, 2018)
During the last ten years, transcatheter aortic valve implantation (TAVI) has become a reliable and valid alternative treatment for elderly patients with severe symptomatic aortic valve stenosis requiring valve replacement and being at high or intermediate risk for surgical risk. While common femoral arteries are the access site of choice in the vast majority of TAVI patients, in up to 15-20% of TAVI candidates this route might be precluded due to the presence of diffuse atherosclerotic disease, tortuosity or small vessel diameter. Therefore, in order to achieve an antegrade or retrograde implant, several alterative access routes have been described, namely trans-axillary, trans-aortic, trans-apical, trans-carotid, trans-septal and trans-caval. The aim of this paper is to give a concise overview on vascular access sites for TAVI, with a particular focus on patient’s selection criteria, imaging, technical aspects and clinical outcome.